ANALISA KEBUTUHAN AIR BERSIH (Studi Kasus PDAM Kabupaten Lombok Utara) - DWI SULISTIA DIA ANGRAENI; MUHAMAD YAMIN; KUSMIANTI KUSMIANTI; ARIANTO ARIANTO (SOSIAL SAINS DAN TEKNOLOGI, 2022)
This study aims to describe (1) the level of clean water availability of PDAM North Lombok Regency in 2025 whether it can meet the needs, and (2) the rate of increase in house connections in the service area of PDAM North Lombok Regency in 2025. This type of research is a case study research with data What is needed in this research is data on the number of house connections, discharge data, and data on water needs. This analysis uses linear regression analysis.The results of the analysis show that the water demand for PDAM in North Lombok Regency in 2025 is 20510.9 m3/year, with a demand of 10796.80 m3/year the number of connections, 10796.82